Shop Stewards, Workers and Managers in Israëli Industry - Kaminka, Shlomit; Rosenstein, Eliezer (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1983)
This paper describes and analyses the place of the shop steward committee in the constellation of relationships at the workplace and pays special attention to the relations between the shop steward committee and the workers.